Institutional Repository in Nigerian Universities: Trends and Development. Issue 3 (2nd April 2017) - Ukwoma, Scholastica C.; Okafor, Victoria N.
ABSTRACT: Promotion and publication of local content on an institutional repository enhances the visibility of the university and staff. This local content consists of the university's publications and other rare materials. As a result of the quality and content of these materials, it is necessary that such resources should be properly preserved for posterity to enhance their access and use. The current article studies the acquisition and management of the contents of five Nigerian universities' institutional repositories available on OpenDOAR. Data was collected using interviews and observation checklist. Study results reveal that University of Nigeria Nsukka has the highest volume of 21, 461 contents, while University of Nigeria Nsukka and Federal University of Technology Akure archived the greatest variety types of content. Covenant and University of Nigeria Nsukka archived more journal articles. The five universities studied acquire their content mainly from their postgraduate schools. These universities have an open-access policy, use DSpace, and apply Dublin Core metadata. The study recommended that creating awareness among universities on the role of institutional repository in enhancing global visibility is important. Therefore, to achieve this, more workshops should be organized.